Islamic Hegemony in Forming Religious Attitudes: Study of Majority and Minority Islam in Southeast Asia - Moh Bashori Alwi Almanduri (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2021)
This article critically examines why the dualism of the Islamic model occurs in Southeast Asia. This article uses a historical approach with the literature method to identify how is the map of the distribution of majority and minority Islam in Southeast Asia, what causes the dualism of the Islamic model in Southeast Asia, and how the minority model occurs in the minority Islamic countries. The results show that Islamic syncretism in the archipelago is a logical consequence of the complicated process of struggling religious reflection. His entity also received many challenges from local Indigenous. The majority of Islam is largely determined by the success of harmonizing Islam with political, social and cultural conditions. On the other hand, poor harmonization with the rulers, military invasion, and colonialism cause Muslim minorities. Islamic minority models can be classified into three parts: First, Separatists, such as the Moro Philippines Muslim Separatist movement. Second, accommodating Pattani Muslims in Thailand and Singapore. Third, Genocide happened to Rohingya Muslims in Burma and Khmer Muslims in Cambodia. Furthermore, research on each minority model can be carried out further to enrich the treasures of Islamic studies in Southeast Asia.Artikel ini menelaah secara kritis mengapa terjadi dualisme model Islam di Asia Tenggara. Artikel ini menggunakan pendekatan historis dengan metode kepustakaan akan mengidentifikasi: Bagaimana peta persebaran Islam mayoritas dan minoritas di Asia Tenggara, apa yang menyebabkan dualisme model Islam di Asia Tenggara, dan bagaimana model keminoritasan yang terjadi pada negara-negara Islam minoritas. Hasil penelitian menunjukkan bahwa Sinkretisme Islam di Nusantara merupakan konsekuensi logis dari proses pergulatan refleksi keagamaan yang rumit. Entitasnya pun banyak mendapatkan tantangan dari Indigeneous lokal. Islam mayoritas sangat ditentukan oleh keberhasilan harmonisasi Islam dengan kondisi politik, sosial, dan budaya. Sebaliknya harmonisasi yang kurang baik dengan penguasa, invasi militer, dan kolonialisme menjadi faktor penyebab minoritas Islam. Model-model minoritas Islam dapat diklasifikasikan menjadi tiga bagian: Pertama, Separatis, seperti gerakan Separatis Muslim Moro Philipina. Kedua, Akomodatif, muslim Pattani di Thailand dan Singapura. Ketiga, Genosida, terjadi kepada muslim Rohingya di Burma dan Muslim Khmer di Kamboja. Selanjutnya penelitian terhadap masing-masing model minoritas bisa dilakukan untuk semakin memperkaya khazanah studi Islam di Asia Tenggara.